Les politiques ouest-européennes et le dollar : Dépendance nationale ou autonomie régionale - Story, Jonathan (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
The lack of autonomy of Western European states, that is, the limitations which they confront in terms of translating their policy preferences into authoritative actions, cannot be considered solely in terms of idiosyncratic domestic political institutions and cultures, or as the result of greater sensibility and vulnerability to interdependence through the flow of goods, capital and technology. The argument develops around the generalisation that during the period of "détente" from 1965 to 1979, the United States, as the world central bank, inflated the world political economy ; thereafter, the questioning of détente accompanied a United States-led policy of world deflation. European politics, in a variety of intricate ways, followed the rythm set by the United States, with a period of state policy activism in the late 1960s to mid-1970s followed by more sceptical attitudes by public officials, supported by conservative or liberal parties, on the limitations of state action. But while it could be argued that the autonomy of OECD European states was strictly limited in economic policy by the integration of national into European and world markets, it is also demonstratable that the most sensitive of these markets - the world financial markets - are most susceptible to state policy, particularly that of the United States. In turn, the influence exerted on government preferences by world financial markets has grown to such an extent that by 1983, Western European governments are all aligning priorities on what are taken to be market criteria. If fact, they are aligning their priorities on the preferences of the great powers in a period of heightened international tension. Thus, the lack of autonomy of Western European states is of political origin: their subordination through lack of continued regional autonomy in defense and finance. Implicitly, this article suggests a move in Western Europe to a confederal armed force and a European Reserve Bank, as the precondition for a revitalised Atlantic alliance.